Technology Integration in BIPA Learning for Beginner Thai Students - Wichayanee Inthase; Imam Suyitno; Gatut Susanto (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Learning Indonesian is very important for Thais who are interested in learning the language to meet the needs of the learners. In addition, the barriers to entry are very limited, resulting in the inability to attend face-to-face classes. Therefore, today's technology is very important in helping teachers and students study anywhere, anytime. This research aims to describe and illustrate the process of learning Indonesian for Thai speakers in Indonesia. The main focus is BIPA, which integrates with technology for Thai speakers. This research is motivated by Indonesia's increasingly high economic growth, which has caused the interest of multinational companies from Thailand to do business in Indonesia. In line with this, the interest and enthusiasm of Thai speakers in learning Indonesian is increasing. The method used in this research was qualitative with the Miles & Huberman interactive model data analysis technique. The data in this research were collected from observations of Indonesian language teaching activities from a sample group of students four Thai speakers who were not able to speak Indonesian yet, to be able to communicate with Indonesian people daily. The research results showed that learning was carried out by utilizing technology in the form of digital applications used in beginner-level BIPA learning, such as Zoom Meeting, Google Meet, Canva, and GoodNote. It was discovered that integrating technology during learning activities can help in teaching, making it more comfortable and allowing to learn anywhere, at any time, and make learning effective. The obstacles in learning include the availability of signals to access learning media.